Towards Vision 2020 -Trends of Cataract Surgery in Melaka Hospital, A Malaysian Tertiary Center: 2007-2014 - Thevi, T.; Abas, A.L. (Kathmandu University Medical Journal, 2020)
Background Cataract surgery which is the only scientific method to treat cataracts has evolved from large incisions of intracapsular cataract excision to extracapsular cataract excision and now modern day phacoemulsification. Anaesthesia too has progressed from general anaesthesia to local and topical anaesthesia. A variety of intraocular lenses are available ranging from rigid to foldable, multifocal and toric. Day care surgeries are becoming the norm these days. Objective Cataract surgery has advanced with new techniques and modalities. We studied the trends of cataract surgery and outcomes over the years. Method We performed secondary data analysis (National Eye Database) of cataract surgery patients in Hospital Melaka (2007 - 2014). Result Most patients were 60-69 years (mean 65.0 years). Primary cataract rose (p<0.05) but there was no difference in laterality and first or second eye (p>0.05). More patients presented with Hypertension and Diabetes (p<0.05). Pterygium encroaching the cornea showed a rise (p<0.05). Phacoemulsification (80.8%) showed a rise while Extracapsular Cataract Extraction (ECCE) (15.4%) declined (p<0.05). More Specialists operated and fewer combined surgeries were performed (p<0.001). Type of anaesthesia did not change (p>0.05). Operative complications reduced (p<0.001). Anterior chamber, scleral fixated and foldable intraocular lenses usage reduced (p<0.05). There was no change in pre-operative visual acuity (p>0.05) but post-operative vision showed a rise in good outcomes (p<0.05). Conclusion Melaka Hospital shows a rise in phacoemulsification and a decline in Extracapsular Cataract Extraction. More patients presented with primary cataracts. More Specialists operated and there was a reduction in intraoperative and postoperative complications. Post-operative visual outcomes showed a remarkable improvement. This improvement is in keeping with the aim of improved vision for all by 2020.